CONTROLLING INFLATION WITH TIMID MONETARY–FISCAL REGIME CHANGES. (9th March 2020) - Ascari, Guido; Florio, Anna; Gobbi, Alessandro
Abstract: Can monetary policy control inflation when both monetary and fiscal policies change over time? When monetary policy is active, a long‐run fiscal principle entails flexibility in fiscal policy that preserves determinacy even when deviating from passive fiscal, substantially for brief periods or timidly for prolonged periods. In order to guarantee a unique equilibrium, monetary and fiscal policies must coordinate not only within but also across regimes, and not simply on being active or passive, but also on their extent. The amplitude of deviations from the active monetary/passive fiscal benchmark determines whether a regime is Ricardian: Timid deviations do not imply wealth effects.